Soil heterogeneity and geogenic-anthropogenic influences on the distribution and ecological risks of potentially toxic elements in semi-arid agricultural soils of north-central Morocco - Ait Mansour, Laila; Boularbah, Ali; Kebede, Fassil (Frontiers in Soil Science, 2025)
Potentially toxic elements (PTEs) in agricultural soils threaten food security and human health, particularly in semi-arid regions where intensive agriculture and limited water resources amplify contamination risks. This study addresses critical knowledge gaps by evaluating PTE distribution, sources, and ecological risks across five representative soil types in north-central Morocco, a region characterized by exceptional pedological diversity including Luvic Phaeozems, Haplic Calcisols, Chromic Luvisols, Vertisols, and Calcic Kastanozems. Unlike conventional regional assessments that apply uniform thresholds, we integrate soil-type-specific analysis to reveal how pedological properties fundamentally control PTE behavior and risk patterns. Fifteen soil samples from 20 horizons across representative pedons and five bedrock samples were analyzed using ICP-OES to quantify nine PTEs (As, Cd, Cu, Mn, Ba, Pb, Sr, Ti, Zn), alongside physicochemical properties (pH, electrical conductivity, organic carbon, texture, cation exchange capacity) to elucidate their influence on metal mobility. Distribution Index, Enrichment Factor, Transfer Factor, and Potential Ecological Risk Index distinguished contamination sources and quantified risks, while Principal Component Analysis identified geochemical associations. Results reveal pronounced soil-type dependency. Luvic Phaeozem exhibited highest contamination, with Cd, As, and Pb exceeding WHO/FAO thresholds and very high ecological risk (PERI>1100). Cd emerged as most mobile, correlating with acidic pH and organic matter. Clay content strongly controlled retention. Multivariate analysis identified anthropogenic contamination with clay retention and carbonate buffering as two main geochemical associations. Principal Component Analysis effectively separated soil types, clustering Luvic Phaeozems and Calcic Kastanozems due to high contamination and retention capacity and isolating Haplic Calcisols and Vertisols for their carbonate and clay-driven buffering behavior. These findings emphasize the necessity of integrating soil typology into risk assessments and recommend targeted bioremediation and soil-type-informed agricultural management to mitigate PTE risks and promote sustainable land use in semi-arid Moroccan agricultural systems.